Cytomorphologic Features Found in Cerebrospinal Fluid Specimens of Hemophagocytic Lymphohistiocytosis Patients: A Report of 64 Cases. Issue 3 (24th February 2021) - Shyu, Susan; Luca, Dragos; VandenBussche, Christopher J; Ho, Cheng-Ying
Abstract: Objectives: Central nervous system involvement is present in 70% of patients with hemophagocytic lymphohistiocytosis (CNS-HLH). CNS-HLH is defined by neurologic deficits, neuroimaging abnormalities, or positive cerebrospinal fluid (CSF) findings. The CSF cytomorphologic spectrum of CNS-HLH, however, has not been well investigated. Methods: A retrospective review was performed on 64 CSF specimens from pediatric and adult patients with HLH. Ten patients had clinicoradiologic evidence of CNS involvement. Results: We identified five CSF cytomorphologic patterns: (1) hemophagocytosis, (2) vacuolated macrophages without evidence of hemophagocytosis, (3) monocytes and/or nonvacuolated macrophages, (4) acellular specimens, and (5) bloody specimens. Patterns 1 and 2 were common in CNS-HLH and rare in patients without CNS involvement. The CSF cytomorphologic patterns did not correlate well with WBC counts or protein concentration. Conclusions: Our study offers a comprehensive view of the cytomorphologic features seen in CSF specimens from patients with HLH.